Roman et Histoire : de la condamnation à la justification : Novel and History: from condemnation to justification - Ibrahim, Laith (Swedish Journal of Romanian Studies, 2025)
During the latter half of the 17th century, both history and the novel fell victim to an identity crisis, finding themselves in a precarious position. On the one hand, historical Pyrrhonism disrupted the way History was perceived, casting doubt on its validity and accuracy. On the other hand, the novel, a disregarded genre lacking literary prestige, was attacked by literary critics with hostility in the name of morality and plausibility. In this delicate situation, historians and novelists unexpectedly, indirectly, and implicitly united to create a fusion between History and the Novel. This fusion filled the void left by History and legitimized the novel genre. This paved the way towards a fertile and inexhaustible ground for revising the historical methodology and establishing the theoretical foundations of the novel. Consequently, the genre of the novel, by turning to History to justify its existence and connecting imaginary events with verified historical facts, transcends the realm of historical discourse. It takes on a sensitivity that unveils not only the official and public History but also the inner motivations of individuals hidden behind political and social issues.